Evasion of the Immune System by Glioblastoma Multiforme: An Obstacle to Achieving Effective Therapies - Kawengian, Kevin Johanes; Wanandi, Septelia Inawati (Cell and BioPharmaceutical Institute, 2024)
Glioblastoma multiforme (GBM), a highly aggressive and malignant form of brain cancer, continues to pose a significant challenge in the field of oncology. Despite ongoing advancements in treatment strategies, the prognosis for GBM patients remains grim, with a 5-year survival rate hovering around 5%. The management of GBM involves multiple therapeutic approaches, including immunotherapy, but optimal treatment outcomes in terms of overcoming tumor recurrence and resistance have not been achieved. A key factor contributing to therapy resistance and the progression of GBM is the tumor's ability to evade the immune system, referred to as immune escape from cancer. This phenomenon reflects the tumor cells' efforts to adapt and survive the body's immune response. The release and expression of molecules like TGF-ß, IL-10, PD-L1, and NKG2DL by GBM cells impact the activation, recognition, and elimination of tumor cells by the immune system. Additionally, the involvement of cells such as MDSCs, Tregs, and TAMs plays a role in inhibiting the immune system's function, thereby promoting the development of GBM cells. A better comprehension of GBM's immune escape, supported by technological advances, will significantly aid in the future management of GBM patients' treatment.Keywords: glioblastoma multiforme, GBM, cancer immunity, immune evasion, immune escape, immunotherapy